A thermokinetic characterization study on combustion of solid biofuels from Aloe vera residue - Kocer, Anil Tevfik (SPRINGER-VERLAG ITALIA SRL, 2023)
Combustion of biomass wastes and solid biofuels obtained from them is a highly preferred and crucial topic in terms of both energy generation and disposal of wastes that cause environmental problems. The objective of this study was to examine the combustion behavior of Aloe vera leaf waste and its biochar samples and to determine the combustion kinetic parameters. The combustion behavior of this waste and biochars at temperatures between 25 and 800 degrees C and heating rates of 5, 10, 20 and 40 degrees C min(-1) was investigated by thermogravimetric method. The combustion kinetic parameters of these samples were calculated using the Kissinger-Akahira-Sunosa (KAS) and Flynn-Wall-Ozawa (FWO) methods. According to the results obtained, since the structure of biomass is more heterogeneous, their combustion mechanism is more complex than that of biochars. The combustion activation energy of Aloe vera wastes was calculated as approximately 285 kJ mol(-1), while the activation energy of biochar was calculated as approximately 150 kJ mol(-1). According to the kinetic and characterization results obtained, it has been understood that biochar samples are a very suitable source for combustion process and they can be evaluated in combustion or co-combustion systems in the future.
Keywords: Aloe vera; Biochar; Combustion; Kinetic; Thermogravimetry; KINETICS; BIOMASS; PYROLYSIS; CARBON; SAWDUST; ENERGY; MANURE; WASTE; Science & Technology - Other Topics